Design, Synthesis and Biological Evaluation of Spiro Cyclohexane-1,2- Quinazoline Derivatives as Potent Dipeptidyl Peptidase IV Inhibitors - Syam, Yasmin M.; El-Karim, Somaia S. Abd; Nasr, Tamer; Elseginy, Samia A.; Anwar, Manal M.; Kamel, Mohsen M.; Ali, Hanan F. (Mini Reviews in Medicinal Chemistry, 2019)
Objective: Inhibition of dipeptidyl peptidase IV (DPP-4) is currently one of the most valuable and potential chemotherapeutic regimes for the medication of Type 2 Diabetes Mellitus (T2DM). Method: Based on linagliptin, this study discusses the design, synthesis and biological evaluation of spiro cyclohexane-1,2'-quinazoline scaffold hybridized with various heterocyclic ring systems through different atomic spacers as a highly potent DPP-4 inhibitors. DPP-4 enzyme assay represented that most of the target compounds are 102-103 folds more active than the reference drug linagliptin (IC50: 0.0005-0.0089 nM vs 0.77 nM; respectively). Moreover, in vivo oral hypoglycemic activity assay revealed that most of the tested candidates were more potent than the reference drug, sitagliptin, producing rapid onset with long duration of activity that extends to 24 h. Interestingly, the derivatives 11, 16, 18a and 23 showed evidence of mild cytochrome P450 3A4 (CYP3A4) inhibition (IC50; > 210 μM) and their acute toxicity (LD50) was more than 1.9 gm/kg. Molecular simulation study of the new quinazoline derivatives explained the obtained biological results. Conclusion: Finally, we conclude that our target compounds could be highly beneficial for diabetic patients in the clinic.
Keywords: linagliptin